2014
DOI: 10.1007/978-3-319-07446-7_57
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Requirements for Textile Input Devices Individually Tailored Interfaces within Home Environments

Abstract: In the last few years, many countries showed an increased public awareness regarding the consequences of the demographic change, which presents considerable challenges on future health care systems in the next decades. As a framework of the research presented here, we introduce a currently running interdisciplinary research project in which novel textile input devices are to be developed, iteratively designed, and evaluated. In order to learn about the individual requirements for using smart textiles in a home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…On the other hand, textiles, provide a promising means to promote robot-human interaction that permit the use of tactile sensors. Textiles are experienced by humans as positive dependent on the qualities of the fabric such as softness, warmth, chicness, colour etc., [26]. As another example, when using clothes to modify the appearance of the humanoid robot ARMAR-IIIb, and studying participants hug the robot, it was shown that the clothed robot brought a positive effect with less discomfort and higher acceptance of the robot [27].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, textiles, provide a promising means to promote robot-human interaction that permit the use of tactile sensors. Textiles are experienced by humans as positive dependent on the qualities of the fabric such as softness, warmth, chicness, colour etc., [26]. As another example, when using clothes to modify the appearance of the humanoid robot ARMAR-IIIb, and studying participants hug the robot, it was shown that the clothed robot brought a positive effect with less discomfort and higher acceptance of the robot [27].…”
Section: Introductionmentioning
confidence: 99%
“…While the sample size overall was adequate for deriving valid findings with a high application potential, still, our sample addressed predominantly younger participants. Given the enormous potential of smart textiles for older users in a medical and care context and older users’ wish to stay longer independently at home [ 27 , 46 ], it is a mandatory claim that older users’ requirements have to be explored in detail in order to make use of smart textiles as innovative technology for seniors [ 47 ]. While both smart products—the smart jacket and the smart arm chair—might be also useful for older persons’ living space, especially when medical care aspects are added to the functional range, it is still questionable whether the dimensions integrated in this study will be sufficient to meet their needs.…”
Section: Discussionmentioning
confidence: 99%
“…Using a scenario-based approach Ziefle et al gathered people’s requirements on interactive textiles for different contexts in the smart home and compared perceived benefits and perceived barriers [ 27 ]. The study revealed both, requirements that apply similarly across the different usage context (e.g., price, durability, and washability) as well as differences: For example, the integration of electronics into carpets was not rated as useful, whereas the usefulness of smart textiles for clothes and furnitures was rated as highest.…”
Section: Related Workmentioning
confidence: 99%